Suicidal intent as a risk factor for mortality in high-level falls: a comparative study of suicidal and accidental falls - Kang, Byung Hee; Jung, Kyoungwon; Huh, Yo (Clinical and experimental emergency medicine, 2021)
Suicide is a major issue in South Korea, and falling is a common method of suicide. Further, accidental falls are a common cause of death. However, whether suicidal falls differ from accidental falls is inconclusive. This study aimed to compare suicidal and accidental falls to identify risk factors for mortality. From March 2010 to December 2016, patients admitted to our hospital because of falls were reviewed retrospectively. Characteristics and outcomes were compared between suicide and accident groups. Injury distribution was compared using the Injury Severity Score and Abbreviated Injury Scales. Multivariate analysis was performed to identify risk factors, including suicide intent, for mortality. Of 242 patients, 42 were included in the suicide group and 200 were included in the accident group. The suicide group showed higher fall heights and injuries of greater severity. The accident group was younger and included a higher number of men. The suicide group showed a higher mortality (23.8% vs. 6.5%, P=0.001) and a higher proportion of injuries in the lower extremities or abdomen. In the multivariate analysis, Glasgow Coma Scale score (0.575 [0.433-0.764], P<0.001), body mass index (1.638 [1.194-2.247], P=0.002), suicide intent (9.789 [1.026-93.404], P=0.047) and Injury Severity Score (1.091 [1.000-1.190], P=0.049) were identified as risk factors for mortality. Suicidal falls were associated with poorer outcomes and a greater tendency to land feet first relative to accidental falls. Suicide intent was a risk factor for mortality.